Discourse and Cognitive Mediation in Teacher Scaffolding: A Psycholinguistic Analysis of Input Processing in Indonesian L2 Learning - Puput Indriani; Gigit Mujianto; Gadis Kartika Pratiwi (PAROLE: Journal of Linguistics and Education, 2026)
This study serves the purpose of assessing the use of scaffolding strategies by teachers in video-based learning from a psycholinguistic perspective and indicators such as intentionality, appropriateness, structure, collaboration, and internalization. Specifically, this study aims to analyse how scaffolding strategies are realized in teacher discourse, how these strategies manifest through the key indicators of scaffolding, and how they correlate with learners’ psycholinguistic processing and understanding of language input. Accordingly, the study addresses the following research questions: (1) how scaffolding strategies are realized in teacher discourse; (2) how these strategies are manifested through the key indicators of scaffolding; and (3) how these strategies relate to learners’ psycholinguistic processing, particularly in directing attention, facilitating input processing, and supporting memory formation. A descriptive qualitative research method was applied with the objective of observing two Indonesian language learning videos. Data were collected indirectly by observing the interactions in the videos, including teachers’ speech Structure and collaboration supported deeper cognitive engagement, whereas internalization reflected the consolidation of input into memory as learners moved toward independent language use. Overall, the success of adapting Indonesian as a second language to digital video-based learning depends on the quality of teacher teaching and the teacher’s ability to think carefully about and implement scaffolding methods adaptively.